Mechanisms for Addressing Space Debris from the Perspective of International Law - Khasanah, Nur Barokah Uswatun; Atsawin, Marc Johan (International Law Discourse in Southeast Asia, 2024)
This paper explores the various mechanisms available for addressing the issue of space debris through the lens of international law. As human activities in space continue to increase, so does the accumulation of space debris, posing significant risks to satellites, spacecraft, and overall space operations. International law plays a crucial role in governing space activities and managing the growing problem of space debris. This paper examines the legal frameworks and mechanisms established at the international level to mitigate, prevent, and manage space debris. It analyzes treaties, agreements, guidelines, and principles relevant to space debris mitigation and explores the roles of different actors, including space agencies, governments, and international organizations, in implementing these mechanisms. The paper also discusses challenges and gaps in current legal frameworks and suggests potential avenues for enhancing international cooperation and coordination in addressing the issue of space debris. Through this examination, the paper aims to contribute to the understanding of the intersection between international law and space debris management and to inform future policy and decision-making in this critical area.